Repertorio de música rock como base para la enseñanza del instrumento de percusión batería del nivel básico superior del colegio de artes “Salvador Bustamante Celi” y su incidencia en el desarrollo interpretativo de los alumnos periodo 2019 – 2020 - Medina Jiménez, Víctor Hugo (2021)
Music is a universal language that makes possible the expression of the deepest emotions between people, it is a didactic resource, which alludes to the immense linguistic diversity of the world. Music has common features that bring people together, as if it were a social interaction, without taking into account differences in age, sex, color or nationality. In the present research work, it was proposed to select a repertoire of rock music for the teaching of percussion and drums, according to the students of the basic superior level of the Salvador Bustamante Celi School of Arts, since rock music, together with other genres of popular music, is an alternative to the contents of the traditional methodologies in the student's musical formation. To achieve this project we proposed as a general objective to contribute with a repertoire of rock music to strengthen the teaching of drums in the students of the “Salvador Bustamante Celi” School of, so we used methods such as: scientific, statistical, analytical and hermeneutic, as well as techniques and instruments such as interview guide and questionnaires that allowed to collect the necessary information from this research work. In addition, we had a total population of 61 people, among which we can mention: 5 authorities of institutions dedicated to musical education, who were interviewed; as well as the survey applied to 6 teachers and 50 students of the drum percussion instrument, members of the educational community, through which we knew how to obtain information about the curriculum, study programs, repertoire corresponding to the level of study, methods used in the process of teaching learning, knowledge and performance of rock music repertoire, these topics contributed to ratify the need to elaborate a didactic text with a repertoire of rock music for the teaching of percussion and drums. It is concluded that, although the importance that the repertoire of rock music has for the teaching of the drum instrument is recognized; nevertheless, the repertoire given to the students is selected to reach certain objective, leaving aside the abilities, skills and taste of the student for topics of rock music, being this a genre that is immersed in the musical daily life of the young people. 5 It is recommended to authorities and teachers of institutions dedicated to the teaching of the drums, to implement as a basis for teaching rock music, as it will be a resource that will facilitate the educational process in students and therefore teachers as a musical pedagogical strategy to work in the classroom, in addition to enjoying music to promote the overall development of students.